Beta band oscillations in the motor thalamus are modulated by visuomotor coordination in essential tremor patients - Basha, Diellor; Kalia, Suneil K.; Hodaie, Mojgan; Lopez Rios, Adriana L.; Lozano, Andres M.; Hutchison, William D. (Frontiers in Human Neuroscience, 2023)
Beta oscillations in sensorimotor structures contribute to the planning, sequencing, and stopping of movements, functions that are typically associated with the role of the basal ganglia. The more recent observation of beta oscillations in the motor thalamus (Vim) indicates that this rhythm may also be involved in pallidal or cerebellar functions such as motor learning and visuomotor adaptation. To test whether STN and/or Vim beta oscillations are involved in such motor tasks, we devised a visuomotor adaptation paradigm whereby ET and PD patients performed a centre-out movement in an inverted computer display. The results show that, in ET, Vim beta oscillations of the LFP were suppressed during the performance of the inverted centre-out task (compared to normal orientation, ANOVA, p<0.05). Interestingly, firing rates increased significantly during periods of low beta power, particularly on approach to the peripheral target (ANOVA, p<0.05). In contrast, beta power in the STN of PD patients did not differ significantly between the inverted and the normal orientation of the centre-out task. The findings support the hypothesis that beta oscillations of the Vim are modulated by novel visuomotor tasks. The inverse relationship between the power of Vim-LFP beta oscillations and Vim firing rates suggest that the suppression of beta oscillations may facilitate information throughput to the thalamocortical circuit by modulation of Vim firing rates.